2014
DOI: 10.1007/s12032-014-0231-1
|View full text |Cite
|
Sign up to set email alerts
|

The importance of cardiovascular risk factors for thrombosis prediction in patients with essential thrombocythemia

Abstract: The current widely accepted stratification defined by age and previous thrombosis in patients with essential thrombocythemia (ET) probably deserves deeper analysis. The aim of our study was to identify additional factors at the time of diagnosis, which have an impact on the thrombosis prediction. We conducted a study of 244 consecutive ET patients with median follow-up of 83 months. We analyzed the influence of age, gender, laboratory parameters, history of previous thrombosis, spleen size, JAK2 mutation as we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 37 publications
2
14
0
Order By: Relevance
“…It is well known that the presence of at least one CV risk factor at diagnosis is associated with significantly higher risk of thrombosis in ET, including global thrombosis and arterial thrombosis confirmed by multivariate model (23)(24)(25).…”
Section: Discussionmentioning
confidence: 65%
“…It is well known that the presence of at least one CV risk factor at diagnosis is associated with significantly higher risk of thrombosis in ET, including global thrombosis and arterial thrombosis confirmed by multivariate model (23)(24)(25).…”
Section: Discussionmentioning
confidence: 65%
“…[17][18][19] Additionally, in agreement with other authors, we found a significant association between splenomegaly and venous thrombosis, and cardiovascular risk factors and a high WBC with arterial thrombosis. 1,7,8,10,16 Interestingly, age ≥ 60 years in our cohort of patients was not a significant risk factor for thrombosis. The lack of correlation between older age and thrombosis was also seen in other recent studies such as those of Lekovic et al 1 and Montanaro et al 20 The presence of JAK2 mutation was not significantly associated with thrombosis in our study, contrary to information well-established in the literature.…”
Section: Discussionmentioning
confidence: 51%
“…1,7,8,10,16 Interestingly, age ≥ 60 years in our cohort of patients was not a significant risk factor for thrombosis. The lack of correlation between older age and thrombosis was also seen in other recent studies such as those of Lekovic et al 1 and Montanaro et al 20 The presence of JAK2 mutation was not significantly associated with thrombosis in our study, contrary to information well-established in the literature. 14,16,[20][21][22] We believe that our small sample size may explain why we found no correlation between thrombosis risk and the presence of JAK2 mutation.…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations